The impacts of the Indonesian Throughflow on the inter‐basin seesaw mechanism, in idealized experiments - Santis, Wlademir; Aimola, Luis; Castellanos, Paola; Campos, Edmo (International Journal of Climatology, 2018)
13 pages, 10 figures, 2 tables, supporting information https://doi.org/10.1002/joc.5424 The role that the Indonesian Throughflow plays on climate is investigated in an alternative scenario, expected during glacial ages. The equatorwards shift of the Southern Hemisphere westerlies found in glacial ages acts to decrease the Agulhas Leakage (AL) and the thermohaline circulation (THC) in the Atlantic. Recent results suggest that these changes are followed by an increased THC in the Pacific, through an inter-basin seesaw mechanism. The enhanced circulation in the Pacific demands thermocline water to cross the equator towards northern latitudes, which shifts the water source of the throughflow from the low-salinity North Pacific to the relative saltier South Pacific. It is shown that in this equilibrium, the salinity anomalies of the throughflow impact the inter-basin seesaw towards the restoration of the modern climate, enhancing the North Atlantic Deep Water (NADW) formation and decreasing the THC in the Pacific. These results are consistent with paleo-observations and provide new insights to interpreting the climate changes in glacial periods. We are very grateful to the Brazilian National Council of Scientific and Technologic Development (CNPq) for the fellowship (140821/2013‐9) and we want specially to acknowledge to the Vale Institute of Technology (ITV) for the financial and academic support to this project. The numerical experiments were also a contribution to Projects SAMOC (grant 2011/5055‐4) and SANSAO (grant 2008/58101‐9), funded by the São Paulo State Foundation for Research Support (FAPESP). Furthermore, the co‐authors acknowledges the Brazilian National Council for Scientific and Technological Development (CNPq) for a Research Fellowship (grant 302018/2014‐0), and the support of the Spanish government, through project VA‐DE‐RETRO (CTM2014‐56987‐P) Peer Reviewed